Facile “scratching” method with common metal objects to generate large-scale catalyst patterns used for growth of single-walled carbon nanotubes - Yu, Ting (2012)
A facile “scratching” method to pattern a catalyst with commonly used metal objects, such as blade, pen cover, tweezers, watchband, knife, key, clamp, and coin, was developed. The single-walled carbon nanotube (SWCNT) networks and well-aligned SWCNT arrays successfully grew by chemical vapor deposition on the scratched catalyst patterns on Si/SiOx and quartz, respectively. This method provides an extremely simple and nearly zero-cost way to fabricate large-scale catalyst patterns used for controlled growth of SWCNT arrays, which could have potential applications in the fabrication of CNT-based devices.